The Influence of Story Telling on Elementary School Children’s Speaking Ability - Dedek Irawan; Meristika Moetia; Puan Tursina (STMIK Indonesia Banda Aceh, 2025)
This quasi-experimental study investigated the effect of the storytelling technique on the English-speaking skills of elementary school students. A purposive sampling method was used to select 29 fifth-grade students each from two classes: Class 5A served as the experimental group, and Class 5B as the control group. The experimental class was taught using the storytelling technique, while the control class received conventional instruction. A pre-test and post-test design was employed to assess students’ speaking abilities, focusing on pronunciation and vocabulary. Data were collected through an oral test consisting of five descriptive questions. The results showed a significant improvement in the experimental group’s speaking performance. The average pre-test score in the experimental group was 23.67, which increased to 66.40 in the post-test, while the control group’s post-test score averaged 57.22. A t-test analysis revealed a statistically significant difference between the groups (t = 2.26 > tₜₐᵦₗₑ = 1.673). These findings suggest that the storytelling technique is effective in enhancing elementary students’ English-speaking abilities, particularly in pronunciation and vocabulary development.